PENGEMBANGAN MEDIA PUZZLE TENTANG MATERI MEMBANDINGKAN BILANGAN PECAHAN UNTUK SISWA KELAS IV SEKOLAH DASAR - Neng Via Fauziah Nur, - (2022)
Factors that cause the low ability of students in understanding comparing fractions such as the lack of attractiveness of the media used so that students' learning motivation is low. This study aims to develop a product in the form of a square puzzle media that is suitable for use as a learning medium in mathematics learning, especially the material for comparing fractions for elementary school students. This study uses the Design Based Research (DBR) method with a model developed by Reeves through four stages: 1) Identification and analysis of problems by researchers and practitioners collaboratively; 2) Develop solution prototypes based on theoretical benchmarks, existing design principles and technological innovations; 3) Undertaking an iterative process to practically test and improve solutions; 4) Reflection to produce design principles and improve implementation of practical solutions. The target of the product trial is the fourth grade elementary school students. The product trial was carried out on June 21, 2022 with 17 fourth grade students (12 female students and 5 male students) as respondents. The subject of product assessment for media feasibility is divided into three experts, namely mathematicians, learning media experts and pedagogical experts. The results of this study are in the form of learning media based on a square puzzle game with a size of 24 x 24 cm. The results of expert validation showed that the fractional puzzle media met the validation criteria of material experts 86.6%, media experts 90.9% and pedagogic experts 93.75% and the trial results with 98.6% results. Based on the results of the overall data analysis, it can be concluded that the fractional puzzle media is appropriate to be used as a learning medium for comparing fractional numbers. Keywords: DBR; Comparing Fractions; Development; Puzzles